Impacts of Permeability Heterogeneity and Background Flow on Supercritical CO2 Dissolution in the Deep Subsurface - Hansen, Scott K.; Tao, Yichen; Karra, Satish (Water resources research, 2023)
Motivated by CO2 capture and sequestration (CCS) design considerations, we consider the coupled effects of permeability heterogeneity and background flow on the dissolution of a supercritical CO2 lens into an underlying deep, confined aquifer. We present the results of a large‐scale Monte Carlo simulation study examining the interaction of background flow rate and three parameters describing multi‐Gaussian log‐permeability fields: mean, variance, and correlation length. Hundreds of high‐resolution simulations were performed using the PFLOTRAN finite volume software to model CO2 dissolution in a kilometer‐scale aquifer over 1,000 years. Predictive dimensionless scaling relationships relating CO2 dissolution rate to heterogeneity statistics, Rayleigh (Ra) and Péclet (Pe) numbers were developed for both gravitationally dominated free convection to background flow‐dominated forced convection regimes. An empirical criterion, Pe = Ra3/4, was discovered for regime transition. All simulations converged quickly to a quasi‐steady, approximately linear dissolution rate. However, this rate displayed profound variability between permeability field realizations sharing the same heterogeneity statistics, even under mild permeability heterogeneity. In general, increased heterogeneity was associated with a lower mean and higher variance of dissolution rate, undesirable from a CCS design perspective. The relationship between dissolution rate and background flow was found to be complex and nonlinear. Dimensionless scaling relationships were uncovered for a number of special cases. Results call into question the validity of the Boussinesq approximation in the context of modest‐to‐high background flow rates and the general applicability of numerical simulations without background flow. Key Points A large Monte Carlo study of the combined effects of background flow and porosity/permeability heterogeneity at field scale was performed Dimensionless relationships for uptake rate scaling and transition between gravitational and forced convection are found Greater heterogeneity reduced expected CO2 uptake and increased its variability. Boussinesq approximation validity is questioned